Collaborative Governance dalam Mitigasi Bencana Banjir di Kabupaten Gresik - Sumina Sumina; Yusuf Hariyoko; Wahid Hidayat (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study is motivated by the high frequency and significant impacts of flooding in Indonesia, particularly the recurrent flooding of the Kali Lamong River in Gresik Regency, which causes substantial socio-economic losses each year. Although disaster management is normatively regulated by national policies, its effectiveness depends largely on collaborative governance among multiple actors. This study aims to analyze the practice of collaborative governance in flood mitigation in Gresik Regency using the model of Weber, Lovrich, and Gaffney (2005), which includes vertical, horizontal, and partnership dimensions, and to identify the key challenges that hinder its implementation. A descriptive qualitative approach was employed in flood-affected areas along the Kali Lamong River, involving BPBD, DPUTR, sub-district governments, village authorities, and local communities through interviews, observations, and document analysis. The findings reveal that collaboration has been established and functions relatively well, particularly in hierarchical coordination, division of roles among government agencies, strengthening of Destana, KENCANA, and SPAB programs, as well as CSR involvement and community participation all contributing to reduced flood duration. However, the implementation of collaborative governance remains constrained by slow land acquisition and infrastructure development, a predominantly reactive orientation, suboptimal early-warning systems between upstream and downstream areas, and uneven support from the private sector and academia. The study concludes that strengthening collaborative mechanisms and accelerating the resolution of structural barriers are essential to achieve more sustainable flood mitigation efforts in Gresik.